Designing of Closed-Loop Supply Chain on Dry Land-Based Catfish Aquabusiness in Gunungkidul: A System Dynamics Approach - Adhita Sri Prabakusuma; Ita Apriani; Budi Wardono; Endy Suwondo; Kuncoro Harto Widodo; Hadi Yahya Saleh Mareeh (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Dry land-based catfish fishery is one of the promising rural aquabusiness in Gunungkidul, Yogyakarta. There are several problems in this business, for example, supply-demand balancing, calculation accuracy of production capacity, and equitable profit distribution to each stakeholder. This research aimed to design a closed-loop supply chain of dry-land catfish industrial-fishery model by employing the system dynamics approach. Powesim Studio 7 coupled MINITAB 14 was applied to measure the robustness of the supply chain management system, to predict optimum production capacity, and to balance profit distribution. A financial analysis was also performed to determine business feasibility. Three scenarios of price were created by considering the predicted trend of catfish consumption and formulated three alternative prices by appraising the juvenile fish production, aquaculture practices, local feedstock manufactured by farmers, and fish-by products distributed by small-enterprises. Those consideration units were constructed of four observed models. The highest profit to stakeholder was obtained by scenario III that was directed to increase the juvenile fish price to Rp 240/fish, consumption-sized fish at the price of Rp 18,000/kg, fish-by product at the price of Rp 150,000/kg, and local feed at the price of Rp 9,000/kg. According to financial analysis, the four subsystems in dry land-based catfish aquabusiness were all feasible by BCR>1; PP was 5-9 years, NPV>0, PI>1, and IRR>15%/year. The implementation of the system required synergetic action among policymakers, farmer cooperative, and local innovation centers.